Supporting digital content marketing and messaging through topic modelling and decision trees - Gregoriades, Andreas; Pampaka, Maria; Herodotou, Herodotos; Christodoulou, Evripides (My University, 2021)
This paper presents a machine learning approach involving tourists’ electronic word of mouth (eWOM) to support destination marketing campaigns. This approach enhances optimisation of a critical aspect of marketing campaigns, that is, the communication of the right content to the right consumers. The proposed method further considers aggregate cultural and economic-related information of the tourists’ country of origin with topic modelling and Decision Tree (DT) models. Each DT addresses different dimensions of culture and purchasing power and the way these dimensions are associated with the topics discussed in eWOM, thus revealing patterns relating tourists’ experiences with potential explanations for their dissatisfaction/satisfaction. The method is implemented in a case study in the context of tourism in Cyprus focusing on two hotel groups (2/3 and 4/5 stars) to account for their differences. Patterns emerged from the extraction of rules from DTs illuminate combinations of variables associated with tourist experience (negative or positive) for each of the two hotel categories and verify the asymmetric relationship between service performance and satisfaction. The approach can be used by management during marketing campaigns to design messages to better address the desires and needs of tourists from different cultural and economic backgrounds, as these emerge from the data analysis.
Keywords: Topic modelling; Cultural and economic distance; Decision trees; Shapley additive explanation; Tourists’ reviews